Perceptions of healthcare access among Lithuanians aged 65 and over during the COVID-19 pandemic - Vytenis Kalibatas; Snieguole Kaseliene; Ramune Kalediene; Olga Mesceriakova; Skirmante Sauliune (Frontiers in Public Health)
AimThis study investigates the perceived accessibility of healthcare services among older adults in Lithuania during the COVID-19 pandemic. The study is significant as it sheds light on geographical, organizational, and financial healthcare access issues encountered by the older population.MethodsConducted in January 2024, the study involved an anonymous questionnaire survey of 1,503 Lithuanian residents aged 65 and older.ResultsThe most frequently utilized healthcare services were consultations with a general practitioner (75.4%) 22.0% of respondents reported not receiving any healthcare services. 53.5% respondents were satisfied with travel time to specialists. Common challenges included difficulties in getting appointments with specialists (53.9%) and dentists (36.2%). Financial barriers led to unmet healthcare needs: 12.6% of the respondents did not receive needed services, 12.8% did not undergo recommended tests, and 14.2% did not purchase prescribed medications. Healthcare services were less accessible to elders with lower education, lower incomes, and those who self-rated health poorly (p < 0.05).ConclusionMost respondents received the healthcare they needed during the pandemic and rated geographical access positively. However, some problems in organizational and financial access were disclosed. The observed social gradient indicates that socioeconomic factors significantly influence healthcare access, potentially increasing vulnerability among certain groups.